ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL EXPENDITURE: DENGAN PENDEKATAN PECKING ORDER THEORY (Studi Empiris pada Perusahaan Manufaktur di BEI) - Dimas Kusuma Adi; Dul Muid (Diponegoro Journal of Accounting, 2013)
This study aims to examine and analyze the effect of internal cash flow, insider ownership, investment opportunity, firm size and growth of sales to capital expenditure.The population in this study is a manufactured company listed on BEI in the period 2005 to 2009. Data was collected through observation method of secondary data. Then a method that includes the classical assumption, hypothesis testing, F test and t test, and analysis of the coefficient of determination (R2). Data analysis using SPSS software version 16.Based on the results of tests performed can be seen that the internal variable cash flow and investment opportunities does not affect the level of capital expenditure. Insider ownership has a negative effect on the level of capital expenditure, meaning more and more ownership of shares owned by insiders, the capital expeditur will be less. Firm size has a positive effect on the level of capital expenditure, meaning that the higher the size of the company, then the capital expenditure will be higher as well. Positive effect on sales growth capital expenditure, meaning that increasing the company's sales growth, the company's capital expenditure will also increase